Subject Matter Limitations in General Sharia Insurance: Comparative Lessons from Indonesia and Malaysia - Aidi, Zil; Khalid, Maryam; Pg Musa, Pg Ismail (LAW REFORM, 2026)
The level of Sharia compliance in a Sharia insurance contract is closely tied to whether the insured subject matter is permissible (halal) or forbidden (haram). This study explores limitations on insurable subject matter under general Sharia insurance from a Sharia perspective and examines the regulatory frameworks in Indonesia and Malaysia that govern these limitations. Adopting a doctrinal and comparative approach, it finds that insurable subject matter must be halal or otherwise permissible under Sharia, with permissibility depending not only on the nature of the subject matter but also on its intended use. The study also reveals differing scholarly opinions regarding the permissibility of specific subject matter within the context of Sharia insurance. Findings further show that neither Indonesia nor Malaysia has clear regulations governing the scope of insurable subject matter, as existing rules are predominantly general and leave the assessment to Sharia insurance operators. The absence of these regulations can lead to divergent perceptions among operators and may erode consumer trust in Sharia insurance products. This study contributes by identifying regulatory gaps in the scope of insurable subject matter under Sharia insurance and by demonstrating the need for clearer regulatory standards to enhance Sharia compliance and legal certainty.